Role of Telemedicine in Rural Areas for Providing Doorstep Medical Treatment to the Elderly and Chronic Disease Patients - HUSSAIN, AYAZ; DAYO, KASHIF ALI; KUMARI, VINEETA; ANJUM, SEHAR; FATIMA, GHULAM; BATOOL, SAMARIA (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Telemedicine has evidently proven to have substantial effect in areas of underserved rural population and can serve as an alternate for the treatment of the chronic disease patients. Aim: To assess the role of telemedicine in rural areas for providing doorstep medical treatment to the elderly and chronic disease patients. Study Design: Prospective study Place and Duration of Study: Ziauddin University, Karachi from 1st July 2024 to 31st December 2024. Methodology: This was performed in the rural far-flung areas of Sindh (Tharparkar, Dadu and Khairpur Mir’s) where not even a rural health care center was provided for a larger catchment population. A total of 1200 elderly cases diagnosed with chronic diseases including diabetes, hypertension as well as cardiovascular diseases and age between 55-75 years were enrolled. They were divided in two groups; each comprised 600 cases (200 from each district). One was considered as control (Group 1) while the other was the experimental group (Group 2). Results: The mean age of the patients in the group 1 and 2 was measured as 61±9.1 and 63±10 years respectively. The majority of the patients in both groups were hypertensive at baseline clinical measurements followed by diabetic and cardiovascular patients. Both groups consolidated results were compared and it was observed that treatment success rate as well as patients stability were not significantly variant within group 1 and 2 (p value 0.87) while there was a significant increase in patients satisfaction in group 2 though telemedicine’s counselling and education. Conclusion: Telemedicine is a transformative solution for chronic disease management in resource-limited rural setting. It demonstrates that remote healthcare interventions can enhance treatment adherence, improve quality of life and address critical access issues.